DIFFRACTIVE HARD PHOTOPRODUCTION AT HERA AND EVIDENCE FOR THE GLUON CONTENT OF THE POMERON - Derrick, M; Krakauer, D; Krakauer, D; Magill, S; Magill, S; Mikunas, D; Mikunas, D; Musgrave, B; Musgrave, B; Repond, J; Repond, J; Stanek, R; et al. (1995)
Inclusive jet cross sections for events with a large rapidity gap with respect to the proton direction from the reaction ep → jet + X with quasi-real photons have been measured with the ZEUS detector. The cross sections refer to jets with transverse energies ET jet > 8 GeV. The data show the characteristics of a diffractive process mediated by pomeron exchange. Assuming that the events are due to the exchange of a pomeron with partonic structure, the quark and gluon content of the pomeron is probed at a scale ∼ (ET jet)2. A comparison of the measurements with model predictions based on QCD plus Regge phenomenology requires a contribution of partons with a hard momentum density in the pomeron. A combined analysis of the jet cross sections and recent ZEUS measurements of the diffractive structure function in deep inelastic scattering gives the first experimental evidence for the gluon content of the pomeron in diffractive hard scattering processes. The data indicate that between 30% and 80% of the momentum of the pomeron carried by partons is due to hard gluons. © 1995.